1994
DOI: 10.1002/mc.2940100403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the genotoxic carcinogen chromium(VI) on basal and hormone‐inducible phosphoenolpyruvate carboxykinase gene expression in vivo: Correlation with glucocorticoid‐and developmentally regulated expression

Abstract: Previous studies have shown that a number of different genotoxic carcinogens that induce different types of DNA damage preferentially alter the expression of inducible genes in vivo. To investigate further the mechanistic basis for these effects, we examined the effects of the human lung carcinogen chromium(VI) on expression of the hormone-inducible cytosolic phosphoenolpyruvate carboxykinase (PEPCK) gene in chick embryo liver. Chromium(VI) pretreatment had significant effects on both basal and glucocorticoid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 35 publications
4
30
0
Order By: Relevance
“…Both the basal and inducible expression of the inducible 5'-aminolevulinate synthase, cytochrome P450 CYP2HI, and phosphoenolpyruvate carboxykinase (PEPCK) genes were markedly affected by the chromium treatment, whereas the albumin, transferrin, and ,-actin genes were refractory to this treatment. The effects on expression of the inducible genes were seen at both the steady-state mRNA and transcriptional levels, and the time courses for these effects closely matched the time course for chromium-induced DNA damage and repair (10,12,14). Interestingly, certain effects most closely correlated with chromium-DNA monoadduct formation, whereas other effects were more closely associated with chromium-DNA cross-link formation (10,12,14).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Both the basal and inducible expression of the inducible 5'-aminolevulinate synthase, cytochrome P450 CYP2HI, and phosphoenolpyruvate carboxykinase (PEPCK) genes were markedly affected by the chromium treatment, whereas the albumin, transferrin, and ,-actin genes were refractory to this treatment. The effects on expression of the inducible genes were seen at both the steady-state mRNA and transcriptional levels, and the time courses for these effects closely matched the time course for chromium-induced DNA damage and repair (10,12,14). Interestingly, certain effects most closely correlated with chromium-DNA monoadduct formation, whereas other effects were more closely associated with chromium-DNA cross-link formation (10,12,14).…”
Section: Introductionmentioning
confidence: 64%
“…Like many organic carcinogens such as benzo [a]pyrene and aflatoxin B1, chromium(VI) appears to act as a classic initiator in these test systems, and this is believed to be the principal mechanism by which chromium(VI) increases carcinogenic risk. Our laboratory has hypothesized that genotoxic carcinogens, including chromium(VI), exert preferential effects on the expression of a specific dass of genes, i.e., inducible genes, as a result of nonrandom DNA damage targeted to members of this gene class (8)(9)(10)(11)(12). Previous studies in our laboratory have shown that a number of different genotoxic chemical carcinogens that induce different types of DNA damage, including the genotoxic metals chromium and nickel, significantly alter both basal and inducible expression of several model inducible genes but have no effect on expression of constitutive genes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complex intracellular reduction chemistry of Cr can produce DNA damage, Cr-mediated DNA adducts, DNA-DNA and DNA-protein crosslinks, and mutations [reviewed in DeFlora et al (4) and Klein (5)]. Cr can also inhibit DNA replication and repair [reviewed in Snow (6)], alter gene expression (7,8), activate stressresponse pathways (2,9), trigger apoptosis (10,11), and damage chromosomes [reviewed in DeFlora et al (4) and Klein (5)]. …”
mentioning
confidence: 99%